Modeling predictors of behavior of American consumers suffering from food intolerances or food allergies. - Marija Cerjak; Marcin Adam Antoniak; Daniela Šálková; Benedykt Pepliński; Sylwester Białowąs; Željka Mesić (PLoS ONE)
Food intolerances, allergies, and celiac disease cause hypersensitive reactions to certain foods, collectively termed adverse reactions to food. This study aims to identify predictors of purchasing intentions and behaviors among individuals with such reactions, using three behavioral models: the Theory of Planned Behavior, the Health Belief Model, and Protection Motivation Theory. The authors created a new, comprehensive model by integrating these theories, combining their strengths to provide a more robust framework. The survey, conducted via the Forthright platform using the Computer-Assisted Web Interview (CAWI) method, involved 1,088 respondents. This article is the first to explore predictors of consumer intentions and behaviors regarding food products suitable for individuals with intolerances or allergies, offering new insights into consumer decision-making models.